2022
DOI: 10.3390/jcdd9020056
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Machine Learning in Patients with Acute Myocardial Infarction

Abstract: (1) Background: Patients with acute myocardial infarction (AMI) still experience many major adverse cardiovascular events (MACEs), including myocardial infarction, heart failure, kidney failure, coronary events, cerebrovascular events, and death. This retrospective study aims to assess the prognostic value of machine learning (ML) for the prediction of MACEs. (2) Methods: Five-hundred patients diagnosed with AMI and who had undergone successful percutaneous coronary intervention were included in the study. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…With the advancement of science and technology, artificial intelligence, gene editing, nanotechnology, and other cutting-edge disciplines, the integration of these technologies and POCT technology in the rapid detection of foodborne pathogens will also become the future development trend ( He et al, 2018 ; Chen et al, 2020c ; Ding et al, 2020 ; Peng et al, 2020b ; Yang et al, 2020c ; Gong et al, 2021 ; Xiao et al, 2022 ). The following is the prospect of POCT technology in the future development trend: 1) the detection index is gradually transformed from biochemical and immunity to nucleic acid molecules, and from single to multiple indicators.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of science and technology, artificial intelligence, gene editing, nanotechnology, and other cutting-edge disciplines, the integration of these technologies and POCT technology in the rapid detection of foodborne pathogens will also become the future development trend ( He et al, 2018 ; Chen et al, 2020c ; Ding et al, 2020 ; Peng et al, 2020b ; Yang et al, 2020c ; Gong et al, 2021 ; Xiao et al, 2022 ). The following is the prospect of POCT technology in the future development trend: 1) the detection index is gradually transformed from biochemical and immunity to nucleic acid molecules, and from single to multiple indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Xiao et al employed six machine learning methods to construct predictive models for the occurrence of major adverse cardiovascular events (MACEs) in AMI patients. The results showed that the best performer was the random forest model, with an AUC of (0.749, 0.644–0.853) [ 47 ]. However, these models did not explore the calibration of the models and the DCA curves, which are very important indicators of the model efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It affects around 40 to 50 million people worldwide, but the number of cases is expected to triple by 2050 due to population growth and aging [ 5 ]. Although many efforts have been made in the past few decades, the complex pathogenesis of the disease remains unclarified, which limits the development of both diagnosis and treatment methods [ 100 , 101 , 102 , 103 ]. The potential of miRNA as biomarkers for early diagnosis of AD has attracted much attention as more and more miRNAs have been found altered in various processes implicated in AD.…”
Section: Roles Of Mirnas In Neurodegenerative Diseasesmentioning
confidence: 99%